Razstava o Ivanu Cankarju Romal sem po široki cesti - Čeh Steger, Jožica; Pulko, Simona; Zemljak Jontes, Melita (Slavia Centralis, 2020)
The authors of the article present an exhibition about Ivan Cankar Romal sem po široki cesti, which was opened on 28 May 2019 in the lobby of the Faculty of Arts in Maribor. It was performed as part of the centenary of Cankar’s death.